Plan de negocios para la creación de una empresa dedicada al ecommerce de los productos de las micro y pequeñas empresas del sector textil en Medellín (2021)
The purpose of the Textil Market business plan is to analyze the viability of creating an ecommerce company for the products of micro and small companies in the Medellín textile sector, in order to promote their growth and strengthening in the market. Data were extracted from the Colombian chamber of electronic commerce, the Medellín chamber of commerce and other entities, in order to analyze the antecedents and problems that organizations present today due to the Covid 19 health emergency, where they have had to take measures to be able to cover the Colombian market without affecting its sales through technology, a logical explanation will be given of who the target customer is and why they were taken into account for the development of the project and additionally the legal process that is 10 required when create an electronic website and the constitution of the company in the Colombian regulatory entities, a market study is carried out through surveys in order to verify the target market that will be obtained where the city of Medellín was chosen since it has with a wide variety of companies in the textile and clothing sector.